Governança das parcerias público-privadas no Brasil: proposta de um modelo teórico-analítico - Lima, Luciano Ferreira de (2017)
The present research argues that the governance of Public-Private Partnerships (PPP) in Brazil can be explained by means of a theoretical-analytical model, based on the assumption of multidimensionality of contracts. To do so, we have investigated the relations between the contractual dimensions of PPP’s governance, through their constructs. The study was conducted in the light of the following theoretical perspectives: Legal Formalism Theory; Transaction Costs Theory; Resource-Based View; Resource Dependence Theory; Stakeholders Theory; and Sociological-based Institutional Theory. Regarding the nature of the research, it is predominantly qualitative, with the combination of quantitative and qualitative methods and procedures, and was carried out in three stages. In the first stage we did a systematic review of the literature on PPP’s governance, based on which we selected the constructs accountability, complexity, cooperation, efficiency, public interest, legitimacy, risk and transparency; and also a bibliometric study to identify authorship by country-year, the main international journals, the density of the author-country-year network, the collaboration network, the density of the collaboration network, and publication by author, among other information. The second stage consisted of 24 in-depth interviews with specialists located in the cities of Curitiba, Brasília, Rio de Janeiro and São Paulo, on the relationships between the constructs identified in the literature. The interviewees are relevant actors in the interorganizational field. Validation of data collected in interviews was done by applying a questionnaire to the specialists, and we used the content analysis technique for data analysis. In the third stage we proposed the theoretical-analytical model, from inferences made due to the multidimensionality of the contracts, the relationships between PPP’s governance constructs and the analysis of interviews. Based on the assumption that contracts are the basic building blocks of society, the results show that PPP’s governance can be explained through the relations of its multiple dimensions. Therefore, we sustain that the different theoretical perspectives have an explanatory power by analytical level (individual, organizational, interorganizational and societal). As a result of the analysis, we present the theoreticalanalytical model that emerges from the interrelationship between the basic categories of PPP’s governance, which are cooperation, legitimacy and efficiency, in a relational-legal continuum.